The first appearance of the Present Perfect tense in EFL coursebooks - Pavlíková, Zuzana (2007)
In this thesis I deal with the first appearance of the Present Perfect tense in coursebooks for EFL students. I analyse and then compare nineteen selected coursebooks which are available on the Czech market and are not older than ten years.